Reliability and validity of icpc-2 for coding/classification of diagnoses/health problems in an African primary care setting - Olagundoye, Olawunmi Abimbola (Stellenbosch : Stellenbosch University, 2017)
Thesis (MMed)--Stellenbosch University, 2017.